THE ADAPTIVE ALGORITHM OF INFORMATION SECONDARY PROCESSING OF THE RF HOMING HEAD - V. A. Malkin; S. A. Glavatskih (Системный анализ и прикладная информатика)
The mode of pointing accuracy of guided missile with RF homing head under the influence of target angle noise is shown in the article. It is achived at the expanse of application of the kinematical link algorithm during reprocessing of angle channel signal wave of homing head. The algorithm is adapted to the changes of noise measurement intensity